Incidência de fungos do gênero Aspergillus seção Circumdati e Nigri em grãos de café cultivados em Minas Gerais e o efeito in vitro de fatores abióticos no crescimento e na biossíntese de ocratoxina A - Oliveira, Gislaine (2016)
Abiotic factors that more influence the growth and the ochratoxin A biosynthesis (OTA) in fungi are the temperature and water activity (aw). In this sense, this study was conducted to evaluate the fungi incidence of the genus Aspergillus, section Circumdati and Nigri, in coffee beans grown in two producing regions of Minas Gerais, besides evaluating the in vitro effect of two abiotic factors (temperature and aw) on the growth and OTA biosynthesis by A. carbonarius and A. ochraceus in synthetic culture coffee base. It was analyzed 14 samples of Arabica coffee beans (Coffea arabica L.), seven of them being of the South of Minas and seven in the Cerrado region of Minas. The identification was based on morphological characteristics. In the isolates, the OTA quantification was performed by high-performance liquid chromatography (HPLC). Ninety (90) fungi of the genus Aspergillus Section Nigri and Circumdati were isolated and identified, of which 82% were owned by section Nigri and 18% belonging to Section Circumdati. In the South region of Minas, the percentage of coffee beans contamination by filamentous fungi was 65.5%. The contamination percentage of the Cerrado samples was 34.5%. In the two regions evaluated, the species most frequently found was A. niger. In this study, 43.24% of isolates belonging to Section Nigri were producers of OTA. Isolates belonging to Section Circumdati, 81.25% were OTA producers. To evaluate the effect of abiotic factors, it was used a central composite design. The Isolates of OTA producers were cultivated on synthetic culture coffee base. A. carbonarius isolates showed the largest increase in aw ranges from 0.935 to 0.965, and temperatures between 25 ° C to 32 ° C. Similarly, the optimum growth conditions for the isolates of A. ochraceus occurred in aw intervals between 0.940 to 0.990, and temperatures between 21 ° C to 30 ° C. The biggest amount of OTA produced by A. carbonarius CCDCA10288 and CCDCA10293 (19.7 to 15.7 μg /g, respectively) was obtained at aw 0.99 and temperature of 15 ° C to 25 ° C. There was a trend for increased OTA production by A. ochraceus CCDCA10211 and CCDCA10212 (8.9-7,9 μg/g, respectively) in aw of 0.98 to 0.99, and temperatures between 25 ° C to 35 ° C and 22 ° C to 32 ° C, respectively. All these information demonstrate that the growth and production of OTA are related to w and temperature. The effect of these factors on OTA production may contribute to the development of models that simulate weather scenarios, providing adaptation strategies.